E-learning Teaching Materials: Accounting Information Systems - Renaldo, Nicholas; Suhardjo, Suhardjo; Sevendy, Tandy (Journal of Applied Business and Technology, 2023)
This study aims to explain further about accounting information systems and serve as reference material for teaching with the e-learning method. This research method is a literature study, analysis of learning needs, development of teaching materials, and evaluation of the effectiveness of the developed teaching materials. Accounting information systems help organizations to collect, store, manipulate, and convey accounting information. This system helps managers to make the right decisions and make income statements more accurate. This system also helps managers to identify and control risks.